2015
DOI: 10.1073/pnas.1508133112
|View full text |Cite
|
Sign up to set email alerts
|

Marine and terrestrial herbivores display convergent chemical ecology despite 400 million years of independent evolution

Abstract: Chemical cues regulate key ecological interactions in marine and terrestrial ecosystems. They are particularly important in terrestrial plant-herbivore interactions, where they mediate both herbivore foraging and plant defense. Although well described for terrestrial interactions, the identity and ecological importance of herbivore foraging cues in marine ecosystems remain unknown. Here we show that the specialist gastropod Elysia tuca hunts its seaweed prey, Halimeda incrassata, by tracking 4-hydroxybenzoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 38 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…The one alga species not affected, Halimeda spp., has strong structural and chemical defenses against most herbivores24 explaining why it alone persisted. Slight decreases in the abundance of Halimeda in the caged treatment may have been due to secondary effects of transplantation, or to the presence of a small Halimeda- specialist herbivore, such as the sea slug Elysia luca 25, which would itself have benefited from the protection of cages. Second, there was a positive response of algal recruitment and growth when herbivory was limited by caging or territorial damselfish in our herbivory x nutrient experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The one alga species not affected, Halimeda spp., has strong structural and chemical defenses against most herbivores24 explaining why it alone persisted. Slight decreases in the abundance of Halimeda in the caged treatment may have been due to secondary effects of transplantation, or to the presence of a small Halimeda- specialist herbivore, such as the sea slug Elysia luca 25, which would itself have benefited from the protection of cages. Second, there was a positive response of algal recruitment and growth when herbivory was limited by caging or territorial damselfish in our herbivory x nutrient experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Liposoluble terpenoids can mediate different alga-herbivore interactions. Halimedatetraacetate is a sesquiterpenoid produced by the green alga Halimeda incrassata identified as a foraging cue for the specialist gastropod Elysia tuca [ 38 ]. As one of the few herbivores that preferentially consume Halimeda species, Elysia may locate its prey by tracking Halimeda -derived chemical cues.…”
Section: Discussionmentioning
confidence: 99%
“…Sacoglossan sea slugs are a group of herbivorous marine gastropods that feed suctorially on siphonaceous green algae. The close relationship that these slugs have with their algal food has caused them to receive some attention for a variety of reasons including their ability to sequester chemical secondary metabolites from host algae (Marin & Ros, 2004), convergent ecological roles similar to terrestrial insects (Rasher et al, 2015) and due to the unusual ability found in some species to sequester algal chloroplasts known as kleptoplasty (reviewed by Pierce & Curtis, 2012; Pierce, Curtis, & Middlebrooks, 2015). Despite interest in some areas of their biology, much about the sacoglossans generally remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%